2016
DOI: 10.12913/22998624/61934
|View full text |Cite
|
Sign up to set email alerts
|

Method of Achieving Accuracy of Thermo-Mechanical Treatment of Low-Rigidity Shafts

Abstract: The paper presents a method combining the processes of straightening and thermal treatment. Technological processes with axial strain were considered, for the case of heated material and without its heating. The essence of the process in the case of heated material consisted in the fact that if under tension all longitudinal forces in the first approximation are uniform -the same strains are generated. The presented technological approach, aimed at reducing the curvature of axial-symmetrical parts, is acceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Analysis of the technology of manufacturing of long shafts with low rigidity, and in particular of the operation of heat treating-straightening [6,7,13], revealed that the drawback of the known technological approaches is the impossibility of keeping the product -shaft -at the state of tension when the temperature is decreased to 20°С, as the fixture is compressed faster than the shaft. Because the walls of the fixture (layered tube or sleeve) are thin (fixture cools down several-fold faster), a gap is formed between the face of the dissected clamping sleeve, which causes the release of the product during cooling, and the appearance of an uneven distribution of inner compressive forces.…”
Section: Methods Of Heat Treating-dtraigh-tening Of Long Shafts With Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the technology of manufacturing of long shafts with low rigidity, and in particular of the operation of heat treating-straightening [6,7,13], revealed that the drawback of the known technological approaches is the impossibility of keeping the product -shaft -at the state of tension when the temperature is decreased to 20°С, as the fixture is compressed faster than the shaft. Because the walls of the fixture (layered tube or sleeve) are thin (fixture cools down several-fold faster), a gap is formed between the face of the dissected clamping sleeve, which causes the release of the product during cooling, and the appearance of an uneven distribution of inner compressive forces.…”
Section: Methods Of Heat Treating-dtraigh-tening Of Long Shafts With Lmentioning
confidence: 99%
“…Shaft-type parts with low rigidity are used in many contemporary machines, fixtures and other devices [1,6,7,8,10,11,12,13,14]. The continuous growth of production of low-rigidity shafts is determined by the growing production of precision machines.…”
Section: Introductionmentioning
confidence: 99%
“…The heat is generated on the microscale when the conduction by the drawing electrons transfer energy to the conductor's atoms by way of collisions [3,6]. The heat can be generated e. g. in resistance wires and it is transferred to the heated object by the conduction, convection and radiation [4,21].…”
Section: Molybdenum Blank Drawing Process Improvementmentioning
confidence: 99%
“…The problem of machining low-rigidity shafts was widely discussed in the literature. There are many publications concerning the problem of stability lobes [2÷23], definition of cutting conditions [4,18], machining forces and error prediction [16,17], surface quality modelling [1,7,11,19] or chatter suppression [15]. Moreover, the problem of simulation of low-rigidity part machining was in the special interests of researchers [5,9,15].…”
Section: Introductionmentioning
confidence: 99%